PENGARUH VARIASI MENU DAN PROMOSI TERHADAP KEPUASAN KONSUMEN PADA ER COFFEE PEKANBARU - Lestari, Rima Kurnia; Safitri, Syofiatul (Komunitas Manajemen Kompetitif, 2025)
The purpose of this study is to determine and explain the menu variation and promotion on consumer satisfaction at Er Coffee Pekanbaru. Consumer satisfaction as the dependent variable, menu variation and promotion as independent variables. This study uses a quantitative approach with accidental sampling, based on coincidence. This study uses a questionnaire distributed to 98 respondents who are consumers of Er Coffee Pekanbaru. The analysis tool used is the SPSS version 30 application. This study uses validity tests, reliability tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression, t-tests, F-tests and determination coefficient tests . The results of this study indicate that, namely: (1) menu variation has a significant effect on consumer satisfaction, (2) promotion has a significant effect on consumer satisfaction, (3) simultaneously, menu variation and promotion have a significant effect on consumer satisfaction. Keywords: Menu Variation, Promotion, Consumer Satisfaction, Quantitative